Flat Panel Angiography Images in the Post-Operative Follow-Up of Surgically Clipped Intracranial Aneurysms. Issue 2 (April 2014) - Budai, Caterina; Cirillo, Luigi; Patruno, Francesco; Dall'Olio, Massimo; Princiotta, Ciro; Leonardi, Marco
Cerebral aneurysms must be monitored for varying periods after surgical and/or endovascular treatment and the duration of follow-up will depend on the type of therapy and the immediate post-operative outcome. Surgical clipping for intracranial aneurysms is a valid treatment but the metal clips generate artefacts so that follow-up monitoring still relies on catheter angiography. This study reports our preliminary experience with volumetric angiography using a Philips Allura Xper FD biplane system in the post-operative monitoring of aneurysm residues or major vascular changes following the surgical clipping of intracranial aneurysms. Volumetric angiography yields not only volume-rendered (VR) images, but a volume CT can also be reconstructed at high spatial and contrast resolution from a single acquisition, significantly enhancing the technique's diagnostic power. Between August 2012 and April 2013, we studied 19 patients with a total of 26 aneurysms treated by surgical clipping alone or in combination with endovascular treatment. All patients underwent standard post-operative angiographic follow-up including a rotational volumetric acquisition. Follow-up monitoring disclosed eight aneurysm residues whose assessment was optimal after surgical clipping both in patients with one metal clip and in those with two or more clips. In addition, small residues (1.3 mm) could be monitored together with any change in the calibre or course of vessels located adjacent to the clips. In conclusion, flat panel volume CT is much more reliable than the old 3D acquisitions that yielded only VR images. This is particularly true in patients with small aneurysm residues or lesions with multiple metal clips.